Analisis Kualitas Fisik Atlet Maluku Platda Ke XX PON Papua Tahun 2021 - Mailopuw, Yenny G. F; Fenanlampir, Albertus (MANGGUREBE: Journal Physical Education, Health and Recreation, 2022)
This study aims to determine the physical quality of the Maluku Pelatda martial arts athletes towards XX Papua PON 2021, the research design used in this study is an evaluative survey with the aim of knowing the physical quality of Maluku Pelatda martial arts athletes towards XX Papua PON 2021, the samples in this study amounted to 15 athletes in martial arts. The variables in this study are stump variables, namely; the quality of physical conditions, test results of research data through norms and converted into tables of physical conditions, thus the results of this study indicate that the physical condition of the Maluku martial arts athletes towards PON XX Papua has a fairly good physical condition.